Is the Concept of Avian Pathogenic Escherichia coli as a Single Pathotype Fundamentally Flawed? - Collingwood, Charlotte; Kemmett, Kirsty; Williams, Nicola; Wigley, Paul (Frontiers in Veterinary Science, 2014)
Avian Pathogenic Escherichia coli (APEC) is a major pathogen within the poultry industry. However disease, especially in broiler chickens, may be caused by range of E. coli genotypes that carry few, if any, virulence factors associated with APEC. Furthermore commensal E. coli in the intestines healthy birds may carry an array of APEC virulence factors suggesting they have potential to cause disease when opportunity arises. Given the diseases caused by APEC, namely colibacillosis and salpingitis peritonitis syndrome, are syndromic in nature and the great diversity of the strains causing disease we suggest it is wrong to consider disease is the result of a single APEC pathotype . Whilst it is clear certain pathogenic E. coli can be considered as APEC, much of the disease associated with E. coli in domestic poultry is as much a consequence of increased host susceptibility due to stress, immunosuppression, co-infection or poor welfare. This leads to more ‘opportunistic’ infections rather than the result of infection with a specific pathotype. As such the current use of the term APEC for all cases of E. coli infection in the chicken is fundamentally flawed.